2015
DOI: 10.1089/ten.tea.2014.0113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brain-Derived Neurotrophic Factor on Mesenchymal Stem Cell-Seeded Electrospinning Biomaterial for Treating Ischemic Diabetic Ulcers via Milieu-Dependent Differentiation Mechanism

Abstract: Great challenges in transplantation of mesenchymal stem cells (MSCs) for treating ischemic diabetic ulcers (IDUs) are to find a suitable carrier and create a beneficial microenvironment. Brain-derived neurotrophic factor (BDNF), a member of neurotrophin family, is considered angiogenic and neuroprotective. Given that IDUs are caused by vascular disease and peripheral neuropathy, we used BDNF as a stimulant, and intended to explore the role of new biomaterials complex with MSCs in wound healing. BDNF promoted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Micronized amniotic membranes have also been used [ 18 ]. Nanofibers containing human BM-MSC [ 32 ], human UC-MSC [ 33 ], or human ADSC [ 63 ] have also been used, as well as fibrin, both in gel to deliver human UC-MSC [ 54 ] and as a spray to deliver BM-MSC [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Micronized amniotic membranes have also been used [ 18 ]. Nanofibers containing human BM-MSC [ 32 ], human UC-MSC [ 33 ], or human ADSC [ 63 ] have also been used, as well as fibrin, both in gel to deliver human UC-MSC [ 54 ] and as a spray to deliver BM-MSC [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…BMSC-conditioned medium activated by neurotrophic factor-3 (NT-3) can promote the proliferation and migration of human umbilical vein endothelial cells (HUVECs) [23] . Brain-derived neurotrophic factor (BDNF), NT-3 and other neurotrophic factors bind to Trk B or Trk C receptors on the surface of BMSCs, activate BMSC paracrine VEGF, FGF and other cytokines, and promote the increase in vascular endothelium, blood vessel density of diabetic skin tissue in C57BL/6J mice cells, and ulcer healing is accelerated [34] . Estrogen stimulates BCPAP papillary thyroid cancer cell lines and ML-1 follicular thyroid cancer cell lines, and it was found that both BCPAP and ML-1 thyroid cancer cells express ER-α and ER-β subtypes of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF induced MSC‐biomaterial complex conditioned medium had higher levels of NGF, MMP9, and IL‐8 resulting in beneficial effects for wound healing …”
Section: Methods To Enhance the Efficacy Of Msc‐based Wound Therapymentioning
confidence: 99%